UPAYA PENGUATAN PENGETAHUAN MASYARAKAT MENGENAI PENYAKIT GANGGUAN SALURAN CERNA FUNGSIONAL PADA ANAK DI PULAU MANDANGIN, KABUPATEN SAMPANG - Subijanto Marto Sudarmo; Alpha Fardah Athiyyah; Andy Darma; Dwiyanti Puspitasari; Khadijah Rizky Sumitro; Ni Nyoman Metriani Nesa; Steven Christian Susianto; Muhammad Faizi; Reza Gunadi Ranuh (Universitas Mataram, 2023)
Functional gastrointestinal disorders are problems that are often experienced by children, especially in isolated areas. Mandangin Island is among the secluded islands located in Sampang district.. The Department of Child Health, Faculty of Medicine, Universitas Airlangga - Dr. Soetomo General Academic Hospital held a community development that aimed to increase public knowledge about functional gastrointestinal disorders in children on Mandangin Island, Sampang District. The community service was conducted using a hybrid seminar approach, where speakers participated remotely via Zoom while the local community gathered at the Village Hall on Mandangin Island.. The speakers explained the definition, important signs and symptoms, early management of Functional Gastrointestinal Disorders. All subjects who took part in community service activities were evaluated for knowledge based on pre- and post-tests, each of which consisted of 5 questions with maximum score 100. Subjectâ€™s knowledge was considered good if the score was â‰¥ 60. Based on our data, there were 29 people who participated in community development with the most working as fishermen and entrepreneurs. We found that 69% of the subjects had an increase in the pre-test score. At the time the pre-test was distributed, only 10.4% had good knowledge scores, while in the post-test there were 51.7% who had good knowledge. We also succeeded in making 3 health cadres caring in childhood functional gastrointestinal disorders. Community development in the form of health education for functional gastrointestinal disorders in children using video conference (ZOOM) on Mandangin Island could increase public knowledge and this activity can be implemented on other islands.